From Reactive to Proactive Safety: Joint Activity Monitoring for Infection Prevention. Issue 1 (October 2022) - Morey, Dane A.; Rayo, Michael F.; Li, Mengyun
Despite the promise of a proactive approach to safety, a lack of resources and tangible measures have limited its implementation in organizations. We are exploring Joint Activity Monitoring (JAM) as one key component of a proactive safety program within the domain of infection prevention. However, despite a conceptual alignment to the requirements of a proactive monitoring capability, our experiences instrumenting daily work tools with the capabilities to support continuous, unobtrusive, real-time monitoring have revealed additional organizational and technological requirements. In this paper, we describe our strategies and challenges in developing this capability and discuss implications for supporting successful proactive safety implementations.